Ijtihad Ra’yu Sahabat dalam Tafsir Al-Qur’an - Yudi Surono; Anita Anita (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
This research aims to find out the position of ijtihad Ra'yu sahabat in the interpretation of the Qur'an.The benefits of this study to improve our knowledge of the opinions, fatwas and ijtihads of friends in this science of qur'an interpretation after the death of the Prophet Muhammad SAW. Hadiths, poles al-turats, opinions of scholars, books of exegesis, suggestions of exegesis and related journals on interpretation in the time of the prophet's companions. The results obtained in this study are that Ijtihat Ra'yu shahabat in the qur'anic interpretation has a high quality, can be used as an argument in the science of tafsir. This is because the ijtihad of the shahabat in interpreting the Qur'an based on their understanding of the events behind the descent of the verse (asbaabunnuzul), thus making them have a deep understanding of the reasonableness, integration and interconnection between one verse of the Qur'an with other verses of the Qur'an and its application in the practice of life.